2017
DOI: 10.1159/000475895
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine and Cannabis Effects on Vital Neurotransmitters and Enzymes in the Brain Tissue of Juvenile Experimental Rats

Abstract: Background: Caffeine and cannabis are globally consumed and abused psychoactive substances. While caffeine is legally used in various forms, including in tea and coffee as beverages, it is also consumed in soda and energy drinks as additives. Cannabis, on the other hand, is considered illegal in most countries; albeit, it is being consumed globally particularly by adolescents. Purpose: The adolescent stage marks a critical stage of brain development and maturation. Influences of agents on the brain at this sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 30 publications
(28 reference statements)
4
18
0
1
Order By: Relevance
“…Excitatory A 2A receptors are mainly in the striatum [46], with an ability to control synaptic plasticity and neurodegeneration [47]. Caffeine affects the release of neurotransmitters, such as norepinephrine, dopamine, acetylcholine, serotonin, glutamate, gamma-aminobutyric acid (GABA) and neuropeptides by blocking the adenosine inhibitory signals through its receptors [48,49], that have significant effects on the perception of alertness and wakefulness besides influencing behavioral and cognitive performance [50,51] (Figure 1). The effects of caffeine are dependent on the dose administered.…”
Section: Caffeine’s Mechanism Of Actionmentioning
confidence: 99%
“…Excitatory A 2A receptors are mainly in the striatum [46], with an ability to control synaptic plasticity and neurodegeneration [47]. Caffeine affects the release of neurotransmitters, such as norepinephrine, dopamine, acetylcholine, serotonin, glutamate, gamma-aminobutyric acid (GABA) and neuropeptides by blocking the adenosine inhibitory signals through its receptors [48,49], that have significant effects on the perception of alertness and wakefulness besides influencing behavioral and cognitive performance [50,51] (Figure 1). The effects of caffeine are dependent on the dose administered.…”
Section: Caffeine’s Mechanism Of Actionmentioning
confidence: 99%
“…[43][44][45] Regarding this, recent studies has demonstrated that caffeine administration increases extracellular dopamine in the striatum in the striatum. 46,47 This indicates that caffeine supplementation may be a potential therapeutic strategy; however, given that maintenance of basal activation of adenosine A1 and A2a receptors plays an important role in antiinflammation, vasodilation, pain modulation, anti-arrhythmia, and metabolic regulation, it is important to understand that the chronic blockage via mega dose (>400 mg per day for adults) of caffeine or pharmacological antagonists against thereceptors may cause several adverse effects.…”
Section: Caffeine Supplementation and Tbimentioning
confidence: 99%
“…39 Following consumption of EDs, Italian young athletes showed a minimal anxiety but no depression. 40 Caffeine, in EDs, is supposed to change the brain chemistry through increasing the activities of the enzymes: cytochrome C oxidase and glucose-6-phosphate dehydrogenase (G-6-PDH), and the neurotransmitters: gamma-amino butyric acid (GABA) and dopamine. 12 The detrimental effects of EDs in Korean youth were assessed to include sleep deprivation, severe stress, depression, and suicide planning and attempts; such effects were more evident in those habitually consuming junk foods.…”
Section: Eds and The Cognitive Mental And Motor Functionsmentioning
confidence: 99%